Gorlin-Goltz Syndrome: Case Report of a Rare Hereditary Disorder - Ashutosh Agrawal; Aditi Murari; Sunil Vutukuri; Arun Singh (Hindawi Limited, 2012)
Introduction. Gorlin-Goltz syndrome is an inherited autosomal dominant disorder with complete penetrance and extreme variable expressivity. Case Report. The present paper highlights the importance of diagnostic criteria and histopathology in early and prompt diagnosis which will lead to proper treatment and genetic counseling of the patient. Discussion. Gorlin-Goltz syndrome is about multisystem process comprising the triad of basal cell nevi, jaw keratocysts, and skeletal anomalies. A spectrum of other neurological, ophthalmic, endocrine and genital manifestations is known to be variably associated with this triad. Diagnosis of the syndrome is based on major and minor criteria. Conclusion. This paper emphasizes the importance of oral and maxillofacial health professionals in the early diagnosis of nevoid basal cell carcinoma syndrome and in a preventive multidisciplinary approach to provide a better prognosis to the patient.